Pengaruh Kompensasi terhadap Kinerja Karyawan pada Kreasindo Jaya Abadi - Elis Silmi; Rudy Susanto; Ismail Dwi Cahyo (Neolectura, 2020)
The purpose of this study was to determine the effect of compensation on employee performance. The method used is a quantitative research method with the number of samples used is 54 respondents. The sampling technique was done by random sampling. The results of the study: The correlation coefficient (rxy) was 0.46. This shows that there is a moderate relationship between the variables of Compensation and Employee Performance at Kreasindo Jaya Abadi; Compensation variable contributes to Employee Performance variable by 21.16% and the remaining 78.84% is contributed by other variables; We get a simple linear regression equation Y = 18.30 + 0.5082X. The results of the hypothesis analysis show the value of t count > t table (3.7353 > 1.6747), so H0 is rejected and Ha is accepted. So, it can be concluded that there is a significant influence between the Compensation variable and the Employee Performance variable.